Pengaruh Kemandirian Belajar Dan Lingkungan Teman Sebaya Terhadap Prestasi Belajar Siswa Kelas VIII SMP Negeri 6 Pematang Siantar Tahun Ajaran 2023/2024 - Daniel Simamora; Sotarduga Sihombing; Anton Luvi Siahaan (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research aims to gain knowledge regarding the influence of independent learning and the peer environment on the learning achievement of class VIII students at SMP Negeri 6 Pematang Siantar in the 2023/2024 academic year. This type of research is qualitative research with a quantitative descriptive data analysis approach with the testing media used is SPSS 24. The total population in this study was 171 people, and the sample used was 120 people. The sampling technique used is simple random sampling. The data collection technique used is a questionnaire (questionnaire). The hypothesis data collection technique uses multiple regression analysis and coefficient of determination (R2). The results of the research state that: 1) There is a positive but not significant influence of learning independence on learning achievement. This result can be seen in the t test where the significant value is 0.429 > 0.05 and the calculated t value of learning independence (0.794) < t table value (1.66159) which means this variable is not significant. 2) There is a positive and significant influence of the peer environment on learning achievement. This result can be seen in the t test where the calculated t value from the peer environment (11.836) > t table (1.66159) which means that this variable is significant. 3) Learning independence and the peer environment together influence learning achievement. This result can be seen in the F test where the Fcount value (3.723) > Ftable value (3.07). The R Square coefficient of determination test was found to be 0.857, which means that 85.7% of the variables of learning independence and peer environment influence student learning achievement at SMP Negeri 6 Pematang Siantar and the remaining 14.3% is the influence of other variables not examined in this research.